Oral health and dental behaviour of patients with left ventricular assist device: a cross‐sectional study - Jens Garbade; Josephine Rast; Gerhard Schmalz; Mirjam Eisner; Justus Wagner; Tanja Kottmann; Andreas Oberbach; Sven Lehmann; Rainer Haak; Michael A. Borger; Christian Binner; Dirk Ziebolz (ESC Heart Failure)
Abstract Aims The aim of this cross‐sectional study was the assessment of dental behaviour, oral health, as well as oral health‐related quality of life of patients with left ventricular assist device (LVAD). Methods and results Patients (128) with LVAD were recruited from the University Department for Cardiac Surgery at Heart Center, Leipzig, Germany. A healthy control group (HC, n = 113) was included. Dental behaviour was assessed with a standardized questionnaire, and to evaluate oral health‐related quality of life, the German short form of oral health impact profile was applied. The presence of decayed, missing, and filled teeth; dental treatment need; periodontitis severity; and periodontal treatment need were assessed. These findings were correlated to disease‐related and device‐related factors. The minority of patients used aids for interdental hygiene (16.4%). For the LVAD patients, a German short form of oral health impact profile sum score of 4.96 ± 8.67 [0.5; 0–6] was assessed. The LVAD group suffered from more missing teeth (11.91 ± 9.13 vs. 3.70 ± 3.77; P < 0.01) than HC. More severe periodontitis was found in LVAD group (LVAD = 41.4% and HC = 27.4%; P < 0.01). Periodontal treatment need was high in both groups, without a significant difference (LVAD = 84.4% vs. HC = 86.7%; P = 0.71). LVAD therapy as bridge to transplantation was correlated with periodontal treatment need (odds ratio = 11.48 [1.27; 103.86]; P = 0.03). Further correlations between treatment need and disease specific factors were not detected. Conclusions Patients with LVAD suffer from a high periodontal treatment need and a lack in oral behaviour. Interdisciplinary special care concepts appear recommendable to improve oral health in LVAD patients.